Analytical methodologies concerning historic neighbourhoods for urban renewal in southern Chile. How to understand the place to intervene? - Niehaus, Matthias; Ibieta, Paulina; Prieto, Andrés J.; Osorio, Emil; Zumelzu, Antonio (Journal of Architecture and Urbanism, 2021)
Historic urban spaces are emplacements that present a particular special interest due to their cultural value and their both urban and architectural pattern. The built environment of cities is composed of a number of variables – anthropic, spatial, morphological, environmental, social, constructive and atmospheric – and all of them must be part of a system that is capable of generating more comfortable and efficient environments. Currently, the work of expert professionals linked to the built environment implies an environmental challenge related to the buildings and their direct harmony with the natural environment; the development of comprehensive plans capable of administering, preserving and protecting historical-heritage constructions in areas susceptible to certain natural disasters; as well as the incorporation of sustainability criteria in urban planning instruments, which is one of the main objectives for regional and state public administrations. This research work intends to propose a comprehensive set of analytical methodologies focused on the morphology of urban blocks, the vitality of the neighbourhood and the functional service life state presented by heritage buildings in order to provide strategies for a proposal for urban regeneration in the case of Barrios Bajos of the city of Valdivia, in southern Chile. This study shows the implications of the proposed methodologies in order to verify their validity and empirically test the application of this type of proposal in one of the historic neighbourhoods of the city of Valdivia, used as a prototype of southern Chile.